The performance of beeswax coating containing vegetable oil-based lecithin as an emulsifier on weight loss and shelf life estimation of mango - NURUL HIDAYATI FITHRIYAH; RATRI ARIATMI NUGRAHANI; RUSNIA JUNITA HAKIM (Jurnal Natural, 2020)
Fruits are one of the agricultural commodities grown in Indonesia and mango constitutes the third largest. One of the disadvantages in transporting mangoes to long distant markets is the short shelf life when fruits are stored at the room temperature. Some efforts to maintain quality and freshness have been coating the fruits with natural wax/beeswax. This study aimed to determine the effects of beeswax coating containing vegetable oil-based lecithin on physical and weight loss in mango, as well as estimate the shelf life using the Accelerated Shelf-Life Testing (ASLT) method. The coating formulation consisted of beeswax, triethanolamine, stearic acid, vegetable lecithin (soybean: rice bran), and water. Mango coated with beeswax coating with a concentration of vegetable lecithin emulsifier were varied at 0.25, 0.5, 0.75, 1%, and control (without beeswax coating) stored at room temperature 301oK and cooler temperature 286oK. Samples were monitored for five weeks and evaluated periodically for physical change and weight loss. Beeswax coated mango exhibited slower rate of ripening than the control stored in both room and cooler temperatures. The lowest total weight loss of mangoes at both temperatures for 5 weeks with beeswax coating at 0.25% vegetable lecithin emulsifier was 7.25%. The estimation of shelf life using ASLT method and Arrheinus model to mango fruit coated with beeswax coating at 0.25% vegetable lecithin concentration as emulsifier was 36.91 days.